Human Papilloma Virus Selftesting as an Alternative Method for Cervical Cancer Screening - Chandra, Richard; Rauf, Syahrul; Malinta, Umar (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the level of acceptance of self Human Papilloma Virus (HPV) examination and to compare the level of sensitivity and specificity of self HPV examination with Fluid Based Cytology on precancerous cervical lesion and cervical cancer. Methods: The analytical method used in this research was cross sectional with purposive sampling. This study is conducted at Wahidin Sudirohusodo Hospital and its affiliation from October 2014 to May 2015 with 101 subjects. The data measurement used self HPV examination tool and fluid based cytology kit. The data collected through questionnaires before and after the examination. The laboratory examination was carried out using the way of HPV Genotyping primary system (MY09/11) method Wl LTS-06, which is able to detect 35 types of HPV viruses. Results: A total of 101 subjects were involved in this study. The subjects were divided into two groups: the abnormal and normal group (n - 50/51). The acceptance level of self HPV examination was 62.37% (n = 63/101). Majority of subjects (88.21%) were ready to repeat the same examination in the future. The level of sensitivity and specificity for self HPV were (56% (95%CI (41.25 - 70.01%)) vs 98% (95%CI (89.55 - 99.95%)), p=<0.000001, while the level of sensitivity and specificity for fluid based cytology were (40% (95%CI (26.41 - 54.82%)) vs 98% (95%CI (89.35 - 99.95%)), p=0.000002. Conclusion: HPV self-testing is very potential to be used as an alternative method for cervical cancer screening. [Indones J Obstet Gynecol 2017; 5-2: 114-119] Keywords: cervical cancer, cervical cancer screening, human papilloma virus, sensitivity, specificity